Real-time template-based tracking of non-rigid objects using bounded irregular pyramids - Marfil-Robles, Rebeca; Bandera-Rubio, Antonio Jesús; Rodríguez-Fernández, Juan Antonio; Sandoval-Hernández, Francisco (IEEE, 2004)
In object tracking, change of objects aspect is the most important cause of failure. This paper proposes a modified template matching approach to solve this problem without a priori leaming of object views. This method permits to track non-rigid objects in real-time by employing a weighted template which is dynamically updated and a hierarchlcal framework that iniegrates all the components of the tracker. The capability of the tracking system to handle partial occlusions and target distortions is demonstrated for several video sequences.
Keywords: Electrónica; Object tracking; Irregular pyramids